The blending of affective domain standards and cognitive domain standards of mathematics with fifth grade at‐risk students - Dean, Alma Jean (Curtin University, 2013)
Prompted by a call for school counselors to become proactive catalysts in the evolution of student achievement, this case study, using largely qualitative data with at-risk fifth grade students, examined the outcomes of blending affective standards with academic standards in mathematics to engender cognitive change. All nine students’ final mathematics grades improved from failing to an average grade of C or better and affective outcomes such as self-reflections and life management skills indicated positive gains.